Rancang Bangun Mesin Pemisah Kulit Kemiri Terintegrasi Komponen Pengering dan Penyaring - Abdul Salam; Abram Tangkemanda; Nashbirullah Nashbirullah; Asriadi Asriadi; Muhammad Farid Fauzan (Politeknik Negeri Ujung Pandang, 2022)
With the traditional method, 1 worker can only produce 1.5 kg/hour of candlenut. When it rains, the candlenut cannot be dried in the sun, so the production of candlenut stops. Candlenut which is not completely dried, cannot produce quality candlenuts when cracked. This study aims to increase the quantity and quality of the candlenut seed production through the design of an integrated drying and filter component of the pecan shell separator using the 3 variable machine capacity test method (drying temperature, drying time and motor rotation) needed to produce optimal conditions for production candlenut. Test This research succeeded in increasing the production of candlenut from 36 minutes/kg to 2.5 minutes/kg. However, this trial has not produced a better quality than the traditional method, where the results of the whole candlenut use 16 % machine, while the traditional method is 70 %. Until now, the best variables we have obtained for separating the candlenut shells on this machine are the drying temperature of 123.4 ⁰C, the drying duration is 60 minutes, and the rotating speed of the motor is 1800 RPM.